Globalization, international law, and human rights - Addicott, Jeffrey F.; Bhuiyan, Jahid Hossain; Chowdhury, Tareq M. R. (New Delhi ; Oxford : Oxford University Press, 2012)
This volume examines human rights in the context of globalisation. It discusses the challenges faced by the international human rights framework from contemporary developments such as climate change, global terrorism, and advances in technology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights; Human rights and globalization